Zadłużenie i płynność finansowa a koszt kapitału - Bereżnicka, Joanna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
The study examines how developed indexes of liquidity and cost of capital in the two companies. The study showed that the level of debt, to a lesser extent, affects the size of the liquidity ratios. Importance in this regard has debt structure. The cost of capital depends on the overall situation in the market (stock price volatility and risk) and not from level of liquidity ratio.